If it's not what You are looking for type in the equation solver your own equation and let us solve it.
48=-7(-6b-8)+4(3-8b)
We simplify the equation to the form, which is simple to understand
48=-7(-6b-8)+4(3-8b)
Reorder the terms in parentheses
48=+(+42b+56)+4*(3-8b)
Remove unnecessary parentheses
+48=+42b+56+4+*(+3-8b+)
Reorder the terms in parentheses
48=+42b+56+(+12-32b)
Remove unnecessary parentheses
+48=+42b+56+12-32b
We move all terms containing b to the left and all other terms to the right.
-42b+32b=+56+12-48
We simplify left and right side of the equation.
-10b=+20
We divide both sides of the equation by -10 to get b.
b=-2
| -5(1-6m)-(4m+2)=-59 | | 7x^2+21x-38=0 | | -2(x-4)=-5(x-4) | | 8(-q-2)+3(q-3)=-20 | | y=4mx+6b | | xy+7x-2y-14= | | 2=-4(1-3k)+3(5k-7) | | y=4mx-2b | | -34+5p=-6-2(3p+3) | | 7+5=2-m | | (x-7)(x+6)=0 | | u+2= | | 3u^2-3= | | 8a+24b= | | (8x+6)+(x+5)= | | u^2-25= | | y=4mx+2b | | 3u-21= | | y=5mx-7b | | 8w+40= | | 2=-4(1-3j)+3(5j-7) | | w^2+3w-10= | | 2=-4(1-3j)+(5j-7) | | 5n^2+35n=0 | | -19=8(g-3)-5(-3+2g) | | (y^2-11y+30)(5y+10)=0 | | 2(x-2)+15=14 | | 8(n-4)-7(n+8)=-80 | | 15x^2+4xy-4y^2= | | 10x+2x+8x-7x+17(x-1)=43 | | 8(h-4)-7(h+8)=-80 | | 7n^2-20n-32=0 |